A computational model to investigate the influence of electrode lengths on the single probe bipolar radiofrequency ablation of the liver. (July 2019) - Cheong, Jason K.K.; Yap, Shelley; Ooi, Ean T.; Ooi, Ean H.
Highlights: The influence of electrode lengths on single probe bipolar RFA is examined. Two cases, lground > lactive and lactive > lground are investigated. Heating was found to be confined to the tissues adjacent to the shorter electrode. Shorter electrode is the limiting factor affecting the mechanics of ablation. Abstract: Background and objectives: Recently, there have been calls for RFA to be implemented in the bipolar mode for cancer treatment due to the benefits it offers over the monopolar mode. These include the ability to prevent skin burns at the grounding pad and to avoid tumour track seeding. The usage of bipolar RFA in clinical practice remains uncommon however, as not many research studies have been carried out on bipolar RFA. As such, there is still uncertainty in understanding the effects of the different RF probe configurations on the treatment outcome of RFA. This paper demonstrates that the electrode lengths have a strong influence on the mechanics of bipolar RFA. The information obtained here may lead to further optimization of the system for subsequent uses in the hospitals. Methods: A 2D model in the axisymmetric coordinates was developed to simulate the electro-thermophysiological responses of the tissue during a single probe bipolar RFA. Two different probe configurations were considered, namely the configuration where the active electrode is longer than the ground and the configuration where the ground electrode is longer than the active. The mathematical model was first verified with an existing experimental study found in the literature. Results: Results from the simulations showed that heating is confined only to the region around the shorter electrode, regardless of whether the shorter electrode is the active or the ground. Consequently, thermal coagulation also occurs in the region surrounding the shorter electrode. This opened up the possibility for a better customized treatment through the development of RF probes with adjustable electrode lengths. Conclusions: The electrode length was found to play a significant role on the outcome of single probe bipolar RFA. In particular, the length of the shorter electrode becomes the limiting factor that influences the mechanics of single probe bipolar RFA. Results from this study can be used to further develop and optimize bipolar RFA as an effective and reliable cancer treatment technique.